THE COURSE IN COMPUTERS–IS IT ACCOUNTING MATHEMATICS? ENGINEERING? - Hein, Leonard W. (The Accounting Review, 1959)
Abstract This article presents information about the course in computers. The era of the lightning-speed calculations of the electronic computer is here and well established. The machine, however, despite the rantings of the press, is not a brain, it needs a brain, a human brain, to instruct and operate it. The human brain, in turn, needs much instruction before it can instruct the machine. Herein lies a problem which must be faced by most of the colleges and universities in the industrialized countries. Course objectives can vary considerably from school to school and even from department to department within a given school. Conceivably a school with a relatively small business department would only want a course which would acquaint its students with the effects of the impact of computers on the business scene, and equip them with the elementary tools to help them cope with those effects when they enter the business world. At the other pole, a department of engineering may be interested in training engineers in computer design principles, with the aim of improving computer design.